2022
DOI: 10.3389/fpsyg.2022.995988
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence, emotional intelligence, and emo-sensory intelligence: Which one is a better predictor of university students’ academic success?

Abstract: The primary aim of this study was to determine the role of psychometric intelligence (IQ), emotional intelligence (EQ), and emo-sensory intelligence (ESQ) in university students’ academic achievement. To this end, 212 university students at different academic levels, composed of 154 females and 58 males, were asked to complete the Raven’s Progressive Matrices, the Bar-On Emotional Quotient Inventory, and the Emo-Sensory Intelligence Scale. Data were then matched with students’ Grade Point Averages as a measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
(50 reference statements)
1
14
0
1
Order By: Relevance
“…Considering the interaction between emotions and senses and their influence on cognition, ESQ can play a vital role in education. Recent research by Pishghadam et al (2022) found that ESQ is a positive predictor of academic success, along with IQ and EQ.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Considering the interaction between emotions and senses and their influence on cognition, ESQ can play a vital role in education. Recent research by Pishghadam et al (2022) found that ESQ is a positive predictor of academic success, along with IQ and EQ.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Having its root in the fundamental assumptions of emotional quotient (EQ) and sensory quotient (SQ), emo-sensory quotient (ESQ) is the ability to recognize, label, monitor, and manage sense-induced emotions to guide one's behavior and establish emo-sensory communication (Pishghadam & Shayesteh, 2017;Pishghadam, Faribi, et al, 2022). In light of the theoretical background presented above and the empirical studies reviewed, the present study seeks to find out the role of gender in emo-sensory intelligence and emo-sensory communication.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…To measure the individuals' level of awareness of their emotions and emo-sensory communicative skills induced by the sensory inputs, the emo-sensory intelligence scale (ESIS) was used (Pishghadam et al, 2020, Pishghadam, Faribi, et al, 2022. This scale, which is in the respondents' native language, consists of 144 items developed to measure the six traditionally well-known senses of hearing, sight, touch, movement, taste, and smell on a five-point Likert-type scale ranging from 1 (very little) to 5 (very much).…”
Section: Instrumentationmentioning
confidence: 99%
“…Emotional intelligence, which has the potential for mental health protection, has received increased attention in recent years ( Mancini et al, 2022 ). The positive impact of emotional intelligence on education has also received widespread attention from practitioners around the world ( Parker et al, 2006 ; Pishghadam et al, 2022 ). Emotional intelligence is the mental ability of individuals to perceive, understand, and assess their own and others’ emotions, as well as to manage, regulate, and apply them ( Salovey and Mayer, 1990 ; Salovey and Grewal, 2005 ; Mayer et al, 2016 ), and is considered a positive factor for psychological well-being ( Schutte et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%